Evolution of national fiscal rules in the European Union countries in the period 2004–2014 (Economic and Political Thought, 2016)
The purpose of this article is an empirical analysis of the evolution ofnational fiscal rules in the European Union countries in the years 2004–2014.Fiscal rules are some of the most important factors affecting the efficiencyof fiscal policy carried out in a country. During the economic crisis, the primaryobjective of fiscal rules is to consolidate public finance, most of all toreduce budget deficit and public debt. The study focuses on the assessmentof changes in the number of national fiscal rules as well as changes in theirquality in the 27 old and new EU countries. It is assumed that the mostimportant factors differentiating the average number of national fiscal rulesapplied in particular countries are: the length of the country’s membershipin the EU, the fiscal mentality of a country, and use of the single currency.The empirical research shows that in the period 2004–2014 the number ofnational fiscal rules in the EU was systematically growing, and their qualitywas improving dynamically. Moreover, it occurred that the above-mentionedfactors are statistically significant determinants of the number of nationalfiscal rules applied by different EU countries.